Destitution, deprivation and tribal `Development' - Pathy, Suguna (2003)
The reasons for the widespread hunger and devastation that Kashipur experienced this year are no different from similar reasons cited for starvation deaths a decade ago. Tribals have been driven into debt with the gradual erosion of their traditional rights to forests and the large-scale intrusion of the usury culture. It is not short-term poverty alleviation programmes or crisis management endeavours that are direly needed, but broader structural interventions that would involve tribals themselves as participants in the development process. - Reproduced.
Keywords: Tribes